2012
DOI: 10.1080/02699931.2012.673477
|View full text |Cite
|
Sign up to set email alerts
|

Anger as “seeing red”: Evidence for a perceptual association

Abstract: Metaphor representation theory contends that people conceptualize their non-perceptual states (e.g., emotion concepts) in perceptual terms. The present research extends this theory to color manipulations and discrete emotional representations. Two experiments (N = 265) examined whether a red font color would facilitate anger conceptions, consistent with metaphors referring to anger to "seeing red". Evidence for an implicit anger-red association was robust and emotionally discrete in nature. Further, Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 45 publications
5
68
2
2
Order By: Relevance
“…One prior study found that physical coldness could significantly increase feelings of a specific emotion: loneliness (Bargh & Shalev, 2012). Another recent study found that people use the color red as a perceptual metaphor to understand anger (Fetterman et al, 2012). Our results add to research showing that metaphors (vertical gaze position and brightness) of emotion can influence, at least temporarily, emotional experience along the pleased-depressed dimension of an observer.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…One prior study found that physical coldness could significantly increase feelings of a specific emotion: loneliness (Bargh & Shalev, 2012). Another recent study found that people use the color red as a perceptual metaphor to understand anger (Fetterman et al, 2012). Our results add to research showing that metaphors (vertical gaze position and brightness) of emotion can influence, at least temporarily, emotional experience along the pleased-depressed dimension of an observer.…”
Section: Discussionsupporting
confidence: 68%
“…However, the idea that environmental input might affect emotion is not entirely novel. Several studies have revealed that color can temporarily influence emotional judgments (Adams & Osgood, 1973;Hevner, 1935;Keith & James, 1975;Valdez & Mehrabian, 1994;Fetterman, Robinson, & Meier, 2012). Within the field of clinical psychology, several studies have shown that phototherapy (daily exposures to bright light) is effective in combating certain depressed disorders, such as seasonal affective disorder (Terman, Terman, & Ross, 1998), antepartum depression (Oren et al, 2002), and general depression (Kripke, 1998).…”
Section: A N U S C R I P Tmentioning
confidence: 97%
“…Blue may be associated with a variety of emotions because the associations are not based upon common physiological reactions. People turn red when they are angry (hence, anger is red), but people do not turn blue when they are sad (Fetterman, Robinson, & Meier, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Third, India is culturally and socially different from the USA. It has different ethnic groups (India is 72 % Indo-Aryan and 25 % Dravidian; the USA is 63.7 % White, 16.3 % Hispanic or Latino, and 12.6 % Black), religions (79.6 % Hindu and 14.2 % Muslim vs. 86.2 % Christian with 24.5 % Catholic and 15.8 % Baptist), (Chen et al, 2014;Fetterman et al, 2012;Waggoner & Palermo, 1989) India (Kennedy, 2011) China (Chen et al, 2014;Yu, 1995) Hungary Japan Matsuki, 1995) Poland (Mikolajczuk, 1998) Zulu language …”
Section: Selecting Countriesmentioning
confidence: 99%
“…Red also shows a strong association with danger (Pravossoudovitch, Cury, Young, & Elliot, 2014). In addition, red is suggested to be associated with negativity (e.g., Gil, & Le Bigot, 2015;Moller, Elliot, & Maier, 2009) and anger (e.g., Fetterman, Robinson, & Meier, 2012;Young, Elliot, Feltman, & Ambady, 2013) but also with warmth and excitement (e.g., Bennett & Rey, 1972).…”
Section: Context-dependency Of the Color Redmentioning
confidence: 99%